Negotiating Multiculturalism: Recentering the Kid Characters’ Voice in Na Willa Dan Rumah Dalam Gang - Nurhadianty Rahayu; Siti Masrifatul Fitriyah; Yanuaresti Kusuma Wardhani; Zahratul Umniyyah (POETIKA, 2026)
Not all children’s books provide the space to examine how children think and interrogate natural, cultural, and social phenomena through their cognitive and communicative lenses. However, Na Willa dan Rumah dalam Gang foregrounds children’s voices that are often overlooked, if not pushed to the periphery. Framing the text as a form of resistance narrative, this study aims to unravel how multiculturality is negotiated through the perspective of the novel’s protagonist and her interactions with adult characters. Given the focus of this study on uncovering the negotiation of multiculturality in a children’s novel, Fairclough’s Critical Discourse Analysis (CDA) framework is employed. Consequently, the findings are structured according to Fairclough’s three levels of discourse meaning-making. The first dimension of textual analysis examines authorial language style and intertextuality as tools for establishing an ideological stance. The second dimension highlights discursive practice in relation to the novel’s production and circulation. The third dimension employs recontextualization of critical multiculturalism (McLaren and Farahmandpur, 1999) to explore how the novel recenters the child as an active subject in meaning-making and in negotiating multicultural issues. In addition to recontextualized critical multiculturalism, the analysis also draws on linguistic and narratological understandings of discourse. This approach helps clarify how the author’s ideological orientation is textually manifested. The findings show that Na Willa dan Rumah dalam Gang situates children’s subjectivity at the centre of meaning-making around diversity, presenting it as a lived and celebrated experience rather than a merely anticipated ideal. Although children’s voices are recentred, adult characters still function as primary moral guides within the narrative. Overall, the study offers a renewed perspective on children’s literature as a medium for reimagining more nuanced forms of critical multiculturalism.